Can You Escape? Creating an Escape Room to Facilitate Active Learning - Adams, Vickie; Burger, Stephanie; Crawford, Kaile; Setter, Robyn (Journal for nurses in professional development, 2018)
Nursing professional development practitioners have the responsibility to find creative and innovative ways to teach and provide learners with the education needed to practice safely in the hospital setting. This article describes an interactive game-based learning experience as a way to engage and empower both nurse residents and experienced nurses.